Statistical analysis of gynecological cancer - Pahwa, Sangeeta; Kaur, Arshdeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Gynaecologic cancers constitute huge burden of morbidity and mortality all over the world. Statistics on gynaecologic malignancies is deficient. It is the leading cause of death and disability worldwide. In India breast cancer ranks number one followed by cervical cancer. The aim of our study was to establish pattern and incidence of gynaecological malignancy. Methods: This hospital based study was conducted in Sri Guru Ramdass Institute of medical sciences and research, Amritsar on 282 patients from March 2020 to December 2020. The demographic data of all cancer patients regarding age, clinical presentation, site, staging, histopathology and treatment given was collected and was analysed in tabulated form. Results: In our study, breast cancer was the commonest malignancy encountered in 46.09% followed by cervical cancer which constituted 32.26%.Ovarian cancer was diagnosed in 15.24%, endometrial cancer in 3.19%, vulval cancer in 2.12% and vaginal carcinomas in 1.06%. Conclusions: Gynaecological cancers are one of the leading causes of cancer related deaths in women worldwide, hence it is important to be aware of various types of malignancies. In our study, cases reported in advanced stages because of lack of education and COVID scenario as patients were reluctant to visit hospitals. So we must continue to provide our gynecologic oncology patient the highest quality of medical care at the same time assuring maximum safety for patients.